Bacteremia due to Acinetobacter ursingii in infants: Reports of two cases - KEPENEKLİ KADAYİFCİ, EDA; YAKUT, NURHAYAT (AFRICAN FIELD EPIDEMIOLOGY NETWORK-AFENET, 2016)
Acinetobacter ursingii is an aerobic, gram-negative, opportunistic microorganism which is rarely isolated among Acinetobacter species. We present two immunocompetent infants who developed bacteremia due to A. ursingii. The first patient is a two -month- old boy who had been hospitalized in pediatric surgery unit for suspected tracheo-esophageal fistula because of recurrent aspiration pneumonia unresponsive to antibiotic therapy. The second patient is a fourteen -month- old boy with prolonged vomiting and diarrhea. A. ursingii was isolated from their blood cultures. They were successfully treated with ampicillin-sulbactam. Although A. ursingii has recently been isolated from a clinical specimen; reports of infection with A. ursingii in children are rare. A. ursingii should be kept in mind as an opportunistic microorganism in children.
Keywords: Bacteremia; acinetobacter ursingii; child; SP-NOV; IDENTIFICATION; BAUMANNII